Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12871-020-01046-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury risk prediction score for critically-ill surgical patients

Abstract: Background: There has been a global increase in the incidence of acute kidney injury (AKI), including among critically-ill surgical patients. AKI prediction score provides an opportunity for early detection of patients who are at risk of AKI; however, most of the AKI prediction scores were derived from cardiothoracic surgery. Therefore, we aimed to develop an AKI prediction score for major non-cardiothoracic surgery patients who were admitted to the intensive care unit (ICU). Methods: The data of critically-il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 28 publications
0
27
0
2
Order By: Relevance
“…Furthermore, extrarenal SOFA score has been identified as independent predictors for AKI in a cohort of non-COVID-19 critically ill surgical patients. [ 47 ] In the setting of SARS-CoV-2 infection, a study conducted on 5216 US veterans provided evidence that older age, male sex and lower baseline eGFR were independent risk factors for AKI during hospitalization. [ 48 ] In parallel to our findings, several studies confirmed that age [ 7 , 49 , 50 ], male gender [ 50 , 51 ], severe COVID-19 (respiratory distress) [ 52 ] and CKD [ 49 , 51 ] were independent risk factors for the development of COVID-19-associated AKI during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, extrarenal SOFA score has been identified as independent predictors for AKI in a cohort of non-COVID-19 critically ill surgical patients. [ 47 ] In the setting of SARS-CoV-2 infection, a study conducted on 5216 US veterans provided evidence that older age, male sex and lower baseline eGFR were independent risk factors for AKI during hospitalization. [ 48 ] In parallel to our findings, several studies confirmed that age [ 7 , 49 , 50 ], male gender [ 50 , 51 ], severe COVID-19 (respiratory distress) [ 52 ] and CKD [ 49 , 51 ] were independent risk factors for the development of COVID-19-associated AKI during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The average AKI prediction score between the derivation and the validation cohorts were significantly different (8.5 ± 3.2 vs. 7.8 ± 3.5 (STD = 0.216) for patients with AKI, and 4.1 ± 2.9 vs. 4.9 ± 2.3 (STD = −0.279) for patients without AKI, respectively). The detailed description of the performance of the AKI prediction score during the derivation was reported in our previous work [ 23 ]. In terms of discriminative ability, the AKI prediction score showed significantly higher discriminative ability in the derivation cohort ( Figure 2 a) than in the validation cohort (STD = 0.245) ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…A screening criterion was used to identify the proper study domain for prediction as follows: adult patients (age equal to 18 and over) who underwent a major non-cardiothoracic operation and were admitted to the ICU for more than 24 hours. A total of 3474 critically ill surgical patients were used during the AKI prediction score derivation [ 23 ]. The incidence of AKI within seven days was 9.6%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations